KONVERGENSI SIMBOLIS DALAM KOMUNIKASI RUANG SIBER - Wildan, Moh (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2014)
The Ministry of ICT (Kominfo) implemented intranet policy for internal organization communications. Every member of the organization or Civitas have a single login access to the portal that serves as a gateway for e-Government applications and public spaces . This study discusses the implementation of public disclosure is implemented through cyber space communications. The Symbolic Convergence Theory that developed by Ernest Bormann used to determine how the construction process of consciousness is formed. The study using qualitative methods with interpretive constructivist perspective. Research conducted during the 3 months of January to March 2014. To obtain validity data are gathered through three ways : observation , Focus Group Discussion ( FGD ) and in-depth interviews of seven informants who have been determined. The results of the study showed a process of dramatization messages that form fantasy chain. Fantasy Type of community and organizations that made up the rhetorical vision : information transparency. Fantasy theme found in the awareness of the process of bureaucratic reform. An efforts makes the Ministry of ICT as leading sector in communications and information technology sector with fantasy theme: Kominfo Gitu Loh!